Pengaruh Globalisasi Terhadap Pengikisan Budaya Bangsa Serta Upaya Pelestariannya - Idah Mujahidah; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
Today, the world has entered an era of globalization where innovative technology enables effective exchange of information and communication between us. However, this globalization phenomenon has led to a number of problems for the younger generation, such as reduced love for their own language and culture. This research aims to understand the influence of globalization on culture and efforts to preserve it. The method used is a literature study with a qualitative approach, using primary and secondary data obtained from various sources such as books, e-books, e-journals and proceedings. The research results show that globalization not only has a positive impact, but also has a negative impact, especially on the continuity of culture in Indonesia which has experienced erosion over time. Efforts to preserve culture that can be carried out by the Indonesian people include in-depth understanding, active interaction, and the provision of information centers related to existing culture.